(3efI GdLdjd aj bHhd Gdhcjds - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s ((3Ydj GdebOSjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdgOGj Edi SHjd GdQTGO hHYO ajbhd CHh GdENdGU MSf GdTQfHdGdj bO hQO SDGd Yf hcjd GOYj HYO ehJ ehcdg EjUGd eG hcdg aj bHVg agd jbHd bhdg aj GdOaY Hjejfg Ce dG HO ef HjfI aCLHJ hSejJg efI GdLdjd aj bHhd bhd Gdhcjd s
(3BNQgG (B:s
(3Ke hLO GdeTJQj HGdYHO YjHG hQOg jQLY HGdKef aj GdJQcI dCfge UGQhG ebQHjf HGdhUhd Edjge MceG cGdEbQGQ ehcd HbHV hcjdg hde jPcQ eMeO QMeg Gddgs
(3LGA aj BNQ GdQSGdI hcJH CUdg ef fSNI HYVgG HNW eDdagG TjN GdESdGe fhQ GdOjf ehdGfG GdTjN Ydj GdebOSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3eYLe GdeDdajf (B1 / 575s
(3EjVGM Gdecfhf (B2 / 567s
(3gOjI GdYGQajf (B1 / 292s
Keywords: (3Gdabg GdMfHdjs